Analysis of Responses to the Use of Kahoot! Interactive Quiz in High School Students on Black Basic Materials - Dea Ramadhana Zsa Zsa Alifah; Titin Sunarti; Oka Saputra (Journal of Digitalization in Physics Education, 2025)
Objective: This study aims to analyze student responses after using the Kahoot interactive quiz on the black principle material. Method: The study was conducted in class XI-2 of Dr. Soetomo Surabaya odd semester of the 2024/2025 academic year. This study uses qualitative descriptive research. Result: The results showed that students responded positively to the use of the Kahoot interactive quiz in learning the black basic materials. Most students felt more enthusiastic, engaged, and motivated during the learning process. They reported that the quiz format helped them better understand the concepts, and the immediate feedback feature allowed them to correct misconceptions quickly. In addition, the competitive yet fun atmosphere increased participation and focus during lessons. Novelty: The Kahoot application presents interesting animations, colors, and sounds, so that learning is not monotonous. Students can find out the ranking after all questions are answered. The development of technology is an opportunity to develop interactive learning media. Therefore, educators are required to provide learning media that make it easier for students to understand the material presented.